Nanocrystals: Synthesis, Properties and Applications - Rao, C.N.R. (Springer Series in Materials Science,, 2007)
Nanocrystals and Their Mesoscopic Organization is an up-to-date monograph on an important aspect of nanoscience and technology. It opens with an elegant introduction including a brief historical account. Emphasis is then given to diverse synthetic methods, both chemical and physical, in addition to modern hybrid methods. The orientation shifts gradually to properties of nanocrystals that evolve with size; detailed discussions are to be found on mesoscalar assemblies in different dimensions, special cases of core-shell and magic nuclearity nanocrystals. The authors also address applications of nanocrystals, carefully separating out potential applications and those that have already emerged, and cite around 900 references from the literature, most from the last decade. Tables providing information at a glance and schematic diagrams at relevant places, make the monograph appealing to read. Occasionally, the reader is reminded of the contributions of celebrated past masters such as Michael Faraday. In summary, the monograph serves as a general introduction as well as a handy reference for the entire community of researchers and practitioners.